Alterations to adipose tissue morphology during inflammatory arthritis is indicative of vasculopathology in DBA/1 mice. (3rd April 2017) - Sime, Katie; Choy, Ernest H.; Williams, Anwen S.
Abstract: The physiologic function of adipose tissue is altered by the host's inflammatory response; the implications for maintaining human health and regulating inflammation-associated disease progression are ill defined. However, this cannot be investigated in humans, therefore the use of animal models is required. With the aim to determine morphological and molecular alterations to perivascular and organ-associated adipose tissues during inflammatory arthritis, collagen-induced arthritis (CIA) was established in male DBA/1 mice. Emerging evidence from this study signposts CIA in the DBA/1 mouse as a model that is relevant to study the development and treatment of early cardiovascular pathology associated with inflammatory arthritis. Here, we show global morphological changes in adipose tissue and the thoracic aorta in animals induced with CIA compared with the non-immunized controls. In CIA, we concluded that the increased cell count in PVAT was, at least in part, caused by an ingress and/or expansion of macrophages that had a mixed phenotype. A substantial increase of galectin-3 was expressed in PVAT from mice with CIA. Galectin-3 is elevated in the blood of patients with CVDs, however, it has never before been measured in PVAT in rodents or humans. Here, PVAT-associated galectin-3 is identified as a potential biomarker for detecting early vascular pathology in CIA and a promising candidate for translation to RA.